2020
DOI: 10.37094/adyujsci.633080
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis of New Schiff Base Compounds and Identification of Their Structures

Abstract: Schiff bases (imines) have been frequently used in various fields such as medicine, pharmaceutical purposes due to their various biological properties. In this study, nine new imine compounds (3a-h) were synthesized from 1-naphthyl amine with aromatic aldehydes in MeOH and their chemical structures were defined by 1H/13C NMR, IR and elemental analysis studies. We observed a singlet one hydrogen of the imines (-CH=N-) at 8.56-8.86 ppm in the 1H NMR spectra and also carbon of the Schiff bases (-CH=N-) at 158.2-1… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 32 publications
0
2
0
Order By: Relevance
“…The study revealed the presence of multiple signals within the range of 6.74-8.56 ppm, corresponding to the number of protons in the prepared ligands, attributed to the aromatic protons. Additionally, a singlet signal at 8.57 and 9.02 ppm was observed, corresponding to the azomethine proton [18] in L1 and L2, respectively, as shown in Fig. 9 and Fig.…”
Section: H 13 Cnmr Spectra Of the Ligandsmentioning
confidence: 83%
“…The study revealed the presence of multiple signals within the range of 6.74-8.56 ppm, corresponding to the number of protons in the prepared ligands, attributed to the aromatic protons. Additionally, a singlet signal at 8.57 and 9.02 ppm was observed, corresponding to the azomethine proton [18] in L1 and L2, respectively, as shown in Fig. 9 and Fig.…”
Section: H 13 Cnmr Spectra Of the Ligandsmentioning
confidence: 83%
“…TLC 3:1 n-hexane: ethyl acetate indicates the end of the reaction in about 10-12 hours. The mono-substituted indole precipitate after reducing solvent, filtered, washed, and dried (20)(21)(22). Two derivatives were synthesized in this step: 2) (0.15 g, 0.00035 mmol) was coupled with 2-deoxy-2-amino-D-glucose according to general procedure mentioned in step-1 above to yield yellow crystals of (2S,3S,4R,5S)-2- and S3).…”
Section: Tools and Instrumentsmentioning
confidence: 99%